CGAS activation causes lupus-like autoimmune disorders in a TREX1 mutant mouse model. (June 2019) - Xiao, Nanyang; Wei, Jingjing; Xu, Shan; Du, Hekang; Huang, Miaohui; Zhang, Sitong; Ye, Weiwei; Sun, Lijun; Chen, Qi
Abstract: TREX1 encodes a major cellular DNA exonuclease. Mutations of this gene in human cause cellular accumulation of DNA that triggers autoimmune diseases including Aicardi–Goutieres Syndrome (AGS) and systemic lupus erythematosus (SLE). We created a lupus mouse model by engineering a D18 N mutation in the Trex1 gene which inactivates the enzyme and has been found in human patients with lupus-like disorders. The Trex1 D18N/D18N mice exhibited systemic inflammation that consistently recapitulates many characteristics of human AGS and SLE. Importantly, ablation of cGas gene in the Trex1 D18N/D18N mice rescued the lethality and all detectable pathological phenotypes, including multi-organ inflammation, interferon stimulated gene induction, autoantibody production and aberrant T-cell activation. These results indicate that cGAS is a key mediator in the autoimmune disease associated with defective TREX1 function, providing additional insights into disease pathogenesis and guidance to the development of therapeutics for human systemic autoimmune disorders. Highlights: The Trex1 D18N/D18N mice recapitulates human AGS and SLE symptoms. Deletion 1 or 2 alleles of cGas gene in the Trex1 D18N/D18N mice rescued all detectable autoimmune phenotypes. This study supports cGAS as a therapeutic target for autoimmune disorders in human.